IMPLEMENTASI PROGRAM PERCEPATAN PEMBANGUNAN KELURAHAN (Studi Kasus di Kelurahan Dusun Baru Kecamatan Seluma Kabupaten Seluma) - Irzani, Irzani (Jurnal Governance dan Administrasi Publik, 2020)
This research was conducted in the village of Dusun Baru Seluma Subdistrict of Seluma Regency. The method used in this research is qualitative descriptive method. Sources of data used is the source of primary data and secondary data relating to the situation and empirical conditions. In this research, the author also uses the research surveys, interviews, and documentation in order to get primary data on the implementation of the accelerated development of the Political district administered of Dusun Baru through Community Participation Enhancement Program in building Political district administered with development activities stimulant Award. The results showed that the implementation of the accelerated development of the Political district administered of Dusun Baru through the implementation of programs increased community participation in building the with the Political district administered development activities stimulant running quite smoothly with the implementation of an increase in governance, community empowerment and development, but if it is linked to the achievement of objectives is not optimal due to the enactment of Law No. 6 of year 2014 about the village and case accelerated development program Political district administered of Dusun Baru had to be stopped because be in contradiction with the Law no. 6 2014 about the village. The conclusion of the implementation of the accelerated development of the Political district administered of Dusun Baru Seluma subdistrict Seluma Regency going well, but This program was stopped because contrary to Law no. 6 of year 2014 on the Political district administered by the Lurah of Dusun Baru community while still expecting the sustainability of this program in building Political district administered infrastructure.